Water Quality Testing On Inconventional Mining Area In Merawang District, Bangka Regency - Guskarnali Guskarnali; Alfitri Rosita; Delita Ega Andini (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2018)
This research about water quality testing on unconventional mining land in Merawang District,Bangka Regency to be used as a water source for fulfilling daily needs for the surroundingcommunity.Sampling is done by purposive sampling by taking into account the considerationof the condition and state of the landscape from the research area. The sample points weretaken as many as 2 samples with different conditions where sample 1 was obtained from thewater under the results of the dominant tin mine tailings in the form of sandstone and claystones and sample 2 from the water under the results of tin mine tailings in the form of kaolin.The taking distance from the two samples is close to about 5 Km. From the results of fielddata collection and laboratory analysis, the pH value in sample 1 was 5.71 and sample 2 was5.57, TSS had a value in sample 1 of 7 mg / L and sample 2 of 8 mg / L, while the TDS valuein sample 1 was 92 mg / L and sample 2 was 8 mg / L. Whereas from laboratory analysis ofdissolved metals obtained values in sample-1 and sample-2 in the form of copper (Cu) havethe same value of 0.0153 and lead (Zn) 0.0531 while sample-2 value of lead dissolved metal(Zn) is 0, 0977. From the chemical and physical parameters and analysis of dissolved metalsif based on the Minister of Health Regulation No. 416 ,1990 about Water QualityRequirements and Supervision and Government Regulation No. 82, 2001 aboutManagement of Water Quality and Water Pollution Control is still classified under the qualitybook and is determined by the value of the Pollution Index based (IPj) on the Decree of theMinister of Environment Number 115,2003 about Guidelines for Determining the Status ofWater Quality. This method is used to determine the level of pollution relative to permittedwater quality parameters. The results obtained indicate that the water quality in the twosamples is categorized as inappropriate (light polluted) as a drinking water qualityrequirement because it has a pollution index value for designation (IPj ) sample-1 was 2.15and sample-2 was 1.86.